Retreatment Strategies in Aneurysm Woven Endobridge Recurrences: A Case Series. Issue 4 (11th April 2022) - Abbas, Rawad; El Naamani, Kareem; Sweid, Ahmad; Birkenstock, Lyena; Ruiz, Ramon; Tjoumakaris, Stavropoula; Gooch, M. Reid; Herial, Nabeel A.; Rosenwasser, Robert H.; Jabbour, Pascal
Abstract : BACKGROUND: The treatment of wide-necked and bifurcation aneurysms has become a common indication for the Woven Endobridge (WEB) device. In many instances, WEB embolization fails and retreatment strategies for the recanalized aneurysms have not been established and may be challenging. OBJECTIVE: To report an experience with retreatment strategies after WEB failure in 7 cases involving various aneurysm shapes, sizes, and location using multiple strategies including endovascular modalities and microsurgical clip ligation. METHODS: Data were retrospectively collected from 1 high-volume cerebrovascular center for 7 patients treated with a WEB device for an aneurysm who subsequently required retreatment for that same aneurysm from 2015 through January 2021. RESULTS: We identified 7 patients with WEB recurrences over a period of 6 years. Four patients initially presented with incidental findings, whereas 3 patients presented with subarachnoid hemorrhage. One patient was lost to follow-up and presented with a rerupture, whereas the 6 other patients were diagnosed with routine follow-up. Two patients received clip ligation, 2 had simple coil embolization, 1 had stent-assisted coil embolization, 1 had a flow-diverting stent, and 1 patient required 2 retreatments; he received stent-assisted coil embolization for the first retreatment and a simple coil embolization for the second retreatment. All patients had excellent angiographic outcomes and no complications. CONCLUSION: The authors conclude that aneurysm recurrence after WEB is very diverse, and no single modality can properly address all recurrences. Rather, an individualized approach based on aneurysm features, neurointerventionalist expertise, and patient preference should be implemented. Abstract :